PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN MODEL CIRCUIT LEARNING DI KELAS V SDN 40 SEI LAREH KOTA PADANG - Ananda Arzeti Rahmadani; Elfia Sukma; Chandra; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was prompted by the less-than-optimal implementation of writing activities in the learning process, which has led to low writing proficiency among fifth-grade students at SDN 40 Sei Lareh, Padang City. The purpose of this research is to describe the enhancement of students' writing skills through the application of the Circuit Learning model in the fifth grade of SDN 40 Sei Lareh, Padang City.The study was carried out using the Circuit Learning model involving one teacher and 19 fifth-grade students as participants. It employed both qualitative and quantitative approaches. This research was categorized as classroom action research (CAR) and was conducted in two cycles. Cycle I consisted of two meetings, while cycle II was conducted in one meeting. Each cycle comprised four stages: planning, implementation, observation, and reflection. Data were collected through tests, non-test techniques, and documentation.The findings indicated an improvement in students’ writing skills. In cycle I, the results showed that: a) the RPPM achieved an average score of 92.5 (B), which increased to 97 (SB) in cycle II; b) the teacher’s implementation aspect in cycle I reached an average of 90 (B) and improved to 95 (SB) in cycle II, while the student aspect also increased from an average of 90 (B) in cycle I to 95 (SB) in cycle II; c) the evaluation of students’ narrative writing skills in cycle I yielded an average score of 72.09 (K), which rose to 84 (B) in cycle II.